PENGARUH KEMAMPUAN PENGELOLAAN PEMBELAJARAN BERBASIS KONSTRUKTIVISME TERHADAP HASIL BELAJAR PKN KELAS V TAHUN PELAJARAN 2018/2019 - Lilia Senja Ilyandani (FIP Unimed, 2018)
ABSTRACT :The purpose of this study was to determine whether there was an effect of the influence of constructivism based of learning management skills on the learning outcomes of students in class V A in the 2018/2019 school year. This research is a quantitative research using survey method. The population in this study were students of class V A totaling 30. Determination of the number of samples was determined using the Slovin formula and obtained a sample of 30 respondents. Data collection techniques in this study use questionnaires. The results of testing the first hypothesis with a partial test (t test) obtained thitung = 3.208> t table = 2.048 with a significance of 0.000 <0.05 means reject Ho and accept H1. Based on these data, it means that the variable constructivism learning has a positive and significant effect on the variables of learning outcomes. Based on these data means the variables of constructivism learning have a positive and significant effect on learning outcomesKeywords: Constructivism, Learning Outcomes.ABSTRAK :Tujuan penelitian adalah untuk mengetahui apakah terdapat pengaruh pengaruh kemampuan pengelolaan pembelajaran berbasis konstruktivisme terhadap hasil belajar mata pelajaran pkn di kelas V A tahun pelajaran 2018/2019. Penelitian ini merupakan kuantitatif dengan menggunakan metode survey. Populasi penelitian ini adalah siswa kelas V A yang berjumlah 30. Jumlah sampel ditentukan menggunakan rumus Slovin dan diperoleh sebesar 30 responden. Teknik pengumpulan data pada penelitian ini menggunakan angket. Hasil pengujian pertama di uji parsial (uji t) diperoleh thitung = 3,208 > ttabel = 2,048 dengan signifikansi 0,000 < 0,05 berarti tolak Ho dan terima H1. Berdasarkan data variabel pembelajaran konstruktivisme berpengaruh secara positif dan signifikan terhadap variabel hasil belajar.